1960
DOI: 10.1111/j.1748-1716.1960.tb01880.x
|View full text |Cite
|
Sign up to set email alerts
|

Myohemoglobin as an Oxygen‐Store in Man

Abstract: ASTRAND, I., P.-0. ASTRAND, E. H. CHRISTENSEN and R. HEDMAN.Myohemoglobin as an oxygen-store in man. Acta physiol. scand. 1960. 48. 454-460. -The aim of the present research was to investigate further the possible r81e of myohemoglobin as an oxygen-store during the initial stage of muscular work. One subject worked intermittently with a work load of 2,520 kpm/min with varied duration of work and rest pauses on a bicycle ergometer. A highly significant difference in the blood lactic acid concentration during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
4

Year Published

1972
1972
2011
2011

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(46 citation statements)
references
References 2 publications
3
39
0
4
Order By: Relevance
“…With 10 sec work periods and 20 see (rest) recovery intervals, Astrand, Astrand, Christensen & Hedman (1960b) found an oxygen lag volume of 430 ml. per 10 sec work period.…”
Section: Discussionmentioning
confidence: 93%
“…With 10 sec work periods and 20 see (rest) recovery intervals, Astrand, Astrand, Christensen & Hedman (1960b) found an oxygen lag volume of 430 ml. per 10 sec work period.…”
Section: Discussionmentioning
confidence: 93%
“…Myoglobin oxygen usage during the work bouts has been estimated to contribute to ϳ44% of the oxygen deficit and has been shown to be resaturated during the rest periods (12). Astrand et al (1) have suggested that myoglobin plays a contributory role as an oxygen store, which supports aerobic metabolism and, presumably, the use of FFAs as a substrate. The source of these FFAs is undetermined, but it has been suggested that intramuscular triacylglycerols (IMTG) stores provide some substrate (32,34).…”
Section: Discussionmentioning
confidence: 99%
“…Astrand and Rodahl [5] drew on earlier data [6,7] to present a table of the relative contribution from the aerobic and anaerobic systems during maximal work efforts ranging from 10 seconds up to 120 minutes. Energy release during the shorter more intense exercise periods was estimated from measures of oxygen deficit, using an assumed mechanical efficiency of 22%.…”
Section: Historical Overviewmentioning
confidence: 99%